Water Quality Notes: Dissolved Oxygen - P. Chris Wilson (EDIS)
SL313, an 8-page illustrated fact sheet by P. Chris Wilson, provides an overview of dissolved oxygen (DO) from a chemical, physical, and ecological perspective and summarizes common analytical methods for measuring DO, state regulations, and management options. Includes glossary and references. Published by the UF Department of Soil and Water Science, January 2010.